1998
DOI: 10.1021/es9704848
|View full text |Cite
|
Sign up to set email alerts
|

Using Cadmium-113 NMR Spectrometry To Study Metal Complexation by Natural Organic Matter

Abstract: Because of its relatively high natural abundance and the broad range of chemical shifts (900 ppm), 113Cd is a potentially excellent istope for NMR studies of metal binding sites of natural organic matter (NOM). This paper presents a 113Cd NMR study of the effects of pH and, to a lesser extent, Cd/C molar ratio on the complexation of cadmium ion by Suwannee River NOM. Spectra are presented for solutions ranging in pH from 3.6 to 9.0 and ranging in Cd/C ratio from 0.0013 to 0.0068. At acidic pH, a single somewha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 14 publications
5
34
1
Order By: Relevance
“…NMR can simultaneously provide information regarding the relative proportions of individual complexes and their electronic environment (i.e. the nature of the donor atoms in the primary coordination shell of the metal ion) (Li et al 1998). The chemical shifts of 113 Cd differ when the metal is coordinated with different ligands (Kostelnik and Bothner-By 1974;see also Fig.…”
Section: Discussionmentioning
confidence: 99%
“…NMR can simultaneously provide information regarding the relative proportions of individual complexes and their electronic environment (i.e. the nature of the donor atoms in the primary coordination shell of the metal ion) (Li et al 1998). The chemical shifts of 113 Cd differ when the metal is coordinated with different ligands (Kostelnik and Bothner-By 1974;see also Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, most of the results confirm the existence of a distribution of dissociation rates of fulvic and humic complexes, with dissociation increasing with increasing metal : humic ratio Lavigne et al, 1987;Cabaniss, 1990;Hering and Morel, 1990;Rate et al, 1993;Chakrabarti et al, 1994;Bonifazi et al, 1996;Lu et al, 1996). The pH also has an important influence on exchange kinetics (Li et al, 1998). Note that the concept of the DEF can be extended to kinetics of Speciation in freshwaters 215 complex dissociation, and that it has been used to compare experimental and predicted curves of dissociation rate constant versus metal : ligand ratio, and to explain why the same fulvic sample may form inert complexes (dissociation in Ն1 day) at low metal : ligand ratios (close to environmental conditions) but labile complexes (dissociation in Յ1 s) at higher ratios (as often used in experimental studies) (Buffle, 1988, Chapter 6).…”
Section: Kinetic Propertiesmentioning
confidence: 87%
“…A number of studies of metallic nuclei have examined: aluminum (Howe et al, 1997 ;Lookman et al, 1997 ;Matthias et al, 2003 ), cesium (Xu et al, 2006 ), vanadium (Lu et al, 1998 ), europium , and lithium (Nielsen et al, 2005 ). However, the most widely applied NMR studies of heavy metals have been the study of cadmium (Chung et al, 1996 ;Larive et al, 1996Larive et al, , 1997Li et al, 1998 ;Otto et al, 2001a,b ;Simpson, 2002 ;Hertkorn et al, 2004 ;Grassi and Daquino, 2005 ;Perdue et al, 2005 ). Cadmium NMR studies have been used to quantify 113 Cd binding (Chung et al, 1996 ;Larive et al, 1996 ;Otto et al, 2001b ), evaluate chemical exchange (Larive et al, 1996 ), identify the groups (mainly oxygen, but also nitrogen and sulfur at certain pH values) responsible for binding (Hertkorn et al, 2004 ), and identify specifi c (inner/outer sphere) complexes (Grassi and Daquino, 2005 ).…”
Section: Contaminant Interactionsmentioning
confidence: 99%
“…The most accessible information in relation to contaminant interactions can be simply inferred from a change in chemical shift of the contaminant species. In the case of metal NMR studies, the observed nucleus is most commonly the metal itself -for example, 113 Cd studies (Dehorter et al, 1992 ;Larive et al, 1996 ;Li et al, 1998 ;Otto et al, 2001a,b ;Hertkorn et al, 2004 ;Grassi and Daquino, 2005 ). In the case of an organic species, many different contaminant nuclei have been studied, including: 1 H Simpson et al, 2004c ), 2 H (Nanny, 1999 ;Nanny and Maza, 2001 ), 13 C (Hatcher et al, 1993 ;Wais et al, 1996 ), 15 N ( Thorn et al, 1996aThorn et al, ,b, 1997Weber et al, 1996 ), and 19 F (Kohl et al, 2000 ;Khalaf et al, 2003 ;Strynar et al, 2004 ).…”
Section: The Chemicalmentioning
confidence: 99%